Salient features of the D3R radar enhancements - Joshil, Shashank S., author; Chandrasekar, V., advisor; Jayasumana, Anura P., committee member; James, Susan P., committee member (Colorado State University. Libraries, 2018)
D3R radar was developed to serve as a ground validation tool for the dual precipitation radar in the core satellite for the Global Precipitation Measurement mission. In order to have more flexibility in operations and improve the features of D3R, the radar was upgraded. Simulations were carried out so that the best design could be determined and implemented on the upgraded D3R (D3R 2.0). The IF subsystems and the digital receiver module which consist of arbitrary waveform generators and the digital receivers of the Ku and Ka bands were changed to support the new features. To enhance signal processing features and make the system compatible with the new design, the D3R software was also upgraded. In this thesis, the design, implementation and tests carried out during the upgrade work for the D3R are presented. The range-velocity ambiguity techniques which work well with low frequency radars pose a challenge in the case of higher frequency radars such as in D3R due to limited Doppler spectrum available. The existing method in D3R to mitigate the range ambiguity problem using random phase codes and staggered PRT is analyzed and the performance of the method is demonstrated for D3R data. The performance of random phase codes and systematic phase codes for range ambiguity mitigation and future changes in D3R 2.0 range ambiguity mitigation technique are discussed. A velocity ambiguity mitigation technique using the dual-frequency information is developed for D3R 2.0; the implementation is explained along with its performance on radar observations. The D3R 2.0 went through initial calibration and testing before being deployed to the ICE-POP field campaign in South Korea. The first results after the upgrade are presented.
Keywords: radar; system; D3R; velocity; range